Application of Smart Rice Transplanter (SRT) to Improve Efficiency and Yield in Agricultural Areas - Salsabila Thifal Nabil Haq; Wahyu Tri Handoko; Moh Zainul Falah; Imam Tree Utomo; Akmah Atikah Amilia; Fuad Indra Kusuma (CV. Creative Tugu Pena, 2024)
Seboro Village is located in Krejengan District, Probolinggo, East Java Province, with an area of ​​94.75 ha (4.50 mi²) consisting of residential land, agricultural land, public facilities, and plantations. The main agricultural products in Seboro Village are rice in the rainy season and tobacco in the dry season. Seboro Village agriculture plays a very important role in maintaining food security because rice is the main raw material for food and also as the main agricultural producer. In the process of planting rice in Seboro Village itself, it is still relatively traditional, only using hands for the planting process in rice fields, so it requires a lot of workers so that the rice seedling planting process is completed quickly. On the other hand, the planting distance between rice seedlings is not the same so that it can interfere with the growth process between rice plants. Therefore, this community service activity proposes a hand-pushed rice planting tool or Smart Rice Transplanter (SRT) which is a tool to help plant rice in agricultural land efficiently and effectively without having to involve many workers. By using the Smart Rice Transplanter (SRT), it can also produce maximum rice harvest production because there is a system for providing planting distance when planting rice seedlings.